Chloroquine, the Coronavirus Crisis, and Neurodegeneration: A Perspective - Pedrioli, Giona; Patani, Rickie; Paganetti, Paolo (Frontiers in Neurology, 2020)
On the verge of the ongoing coronavirus pandemic, in vitro data proposed that chloroquine, and its analogue hydroxychloroquine, may be useful in controlling SARS-CoV-2 infection. Efforts are ongoing in order to test this hypothesis in clinical trials. Some studies demonstrated no evidence of efficacy, whereas in some cases results were retracted after reporting. Despite lack of scientific validation, support for the use of these compounds continues from influencers in the medical and lay domain. At the cellular level, the lysosomotropic drug chloroquine accumulates in acidic organelles where it acts as an alkalizing agent with possible downstream effects on several cellular pathways. In this perspective, we discuss a possible modulatory role of the drugs on two shared features of neurodegenerative diseases, the cellular accumulation of aberrantly folded proteins and the contribution of neuroinflammation in this pathogenic process. Certainly, the decision on the use of chloroquine must be determined by its efficacy, clinical needs and depending on symptoms. However, at an unprecedented time of a potential widespread use of chloroquine, we seek to raise awareness for a careful documentation in the use of this drug as it may potentially lead to misinterpretation in ongoing clinical trials evaluating disease-modifying therapies in neurodegeneration.